Proses Pembuatan Sertipikat atas Tanah Negara Menjadi Hak Milik Akibat Peralihan Jual Beli di Kantor Pertanahan Kota Jakarta Barat (Lex Jurnalica, 2011)
Along with the growing population, demand for land continues to increase. Those needs sometimes lead to conflicts of interest so that land becomes a problem often faced by society. In carrying out the process pensertifikatan state land becomes the property should be based on legislation and regulations. But the practice, there may be irregularities. This research want to discuss about how the process of making the certificate on state land becomes the property of the transition due to buying and selling in the office of the Land West Jakarta City? and what obstacles it faced in the implementation of the manufacture of certificate of state land becomes the property of the transition due to buying and selling in the office of the Land west of Jakarta? In making this the author uses the methods of normative legal research using primary legal materials that the author got from library research. From the survey results revealed that the process pensertifikatan state land becomes the property of the transition due to be implemented by way of individual rights by attaching all the requirements of the petition and brought to the Land Office to subsequently issued certificate. And note also that the obstacles encountered in the process that is difficult to achieve agreed pensertifikatan from citizens, bureaucratic maze of government officials, many costs that are not clearly collected from residents. Solution of the obstacles encountered in the process pensertifikatan ie increased awareness of citizens, a more strict regulations governing the cost and strict sanctions.Keywords: Certified, Land, Trading